Persepsi Masyarakat Terhadap Implementasi Tri Hita Karana Dalam Penataan Ruang Pemukiman di Denpasar Selatan - Sarjana, I Putu (Jayapangus Press, 2023)
The establishment of settlements in Bali is based on the Tri Hita Karana (THK) philosophy. However, the implementation of THK in residential spatial planning has now experienced a shift, especially in urban areas. Many settlements in the South Denpasar area do not use the THK concept. This study aims to analyze people's perceptions of the implementation of THK in residential spatial planning in South Denpasar. The research method used is qualitative research with data collection techniques namely observation, in-depth interviews and document studies. Data analysis was carried out in an interpretive descriptive manner. The results of the study show that in the South Denpasar region there are three models of residential environments, namely geria/puri/jero settlements, naturally developing settlements, and settlements built by developers. The geria/puri/jero settlements still maintain Balinese Traditional Architecture (ATB) according to THK, while the general population and settlements built by developers tend not to comply with THK. The Balinese Hindu community residents of settlements in South Denpasar have the perception that a place to live in must be in harmony with the local natural environment, and adhere to the concept of ATB and the THK philosophy. However, due to limited land, the community admits that they cannot fully apply the ATB concept. In conclusion, the implementation of the THK concept in residential spatial planning in South Denpasar cannot be fully implemented due to limited residential land.